Assessment of quality and pre-clinical efficacy of a newly developed polyvalent antivenom against the medically important snakes of Sri Lanka - Aparup Patra (Nature Portfolio, 2021)
Abstract Snake envenomation is a severe problem in Sri Lanka (SL) and Indian polyvalent antivenom (PAV) is mostly used for treating snakebite albeit due to geographical variation in venom composition, Indian PAV shows poor efficacy in neutralizing the lethality and toxicity of venom from the same species of snakes in SL. Therefore, the quality and in vivo venom neutralization potency of a country-specific PAV produced against the venom of the five most medically important snakes of SL (Daboia russelii, Echis carinatus, Hypnale hypnale, Naja naja, Bungarus caeruleus) was assessed. LC-MS/MS analysis of two batches of PAV showed the presence of 88.7–97.2% IgG and traces of other plasma proteins. The tested PAVs contained minor amounts of undigested IgG and F(ab′)2 aggregates, showed complement activation, were devoid of IgE, endotoxin, and content of preservative was below the threshold level. Immunological cross-reactivity and in vitro neutralization of enzymatic activities, pharmacological properties demonstrated superior efficacy of SL PAV compared to Indian PAV against SL snake venoms. The in vivo neutralization study showed that the tested PAVs are potent to neutralize the lethality and venom-induced toxicity of SL snake venoms. Therefore, our study suggests that introduction of SL-specific PAV will improve snakebite management in SL.